Grand challenges for the study of cultural evolution - Brewer, J; Gelfand, M; Jackson, J; MacDonald, I; Peregrine, P; Richerson, P; Turchin, P; Whitehouse, H; Wilson, D (Springer Nature, 2017)
The founding members of the Cultural Evolution Society were surveyed to identify the major scientific questions and ‘grand challenges’ currently facing the study of cultural evolution. We present the results and discuss the implications for an emergent synthesis in the study of culture based on Darwinian principles.